(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents a significant extension of the classical TODIM (an acronym in Portuguese for Interactive and Multicriteria Decision-Making) method, originally grounded in prospect theory, by integrating it with Complex Cubic Fuzzy data to form a novel decision-making framework, CCF-TODIM. The primary contribution lies in extending the classical TODIM technique by incorporating CCF sets, which offer a more expressive representation of uncertainty by simultaneously capturing membership, non-membership, hesitation, and complex evaluations. The proposed CCF-TODIM method is systematically developed, and its operational steps are detailed through a comprehensive numerical example. To demonstrate practical relevance and robustness, the framework is applied to a real-world case study that assesses the global economic impacts of the Afghan-American War. A comparative analysis with existing MADM approaches reveals the superiority of the CCF-TODIM model in terms of accuracy and adaptability. Furthermore, the impact of different distance measures on the final ranking of alternatives is investigated to validate the sensitivity and stability of the method. The study establishes CCF-TODIM as a powerful tool for handling ambiguous and complex decision environments, with broad applicability in socio-economic and geopolitical analysis.